Subgenomic RNA Abundance Relative to Total Viral RNA Among Severe Acute Respiratory Syndrome Coronavirus 2 Variants. (10th November 2022) - Su, Maxwell; Ping, Sara; Nguyen, Phuong-Vi; Rojas, Alejandra; Hussaini, Laila; Carmola, Ludy Registre; Taz, Azmain; Sullivan, Julie; Martin, Greg S; Piantadosi, Anne; Martinez, Magaly; Lam, Wilbur A; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) subgenomic RNA (sgRNA) may indicate actively replicating virus, but sgRNA abundance has not been systematically compared between SARS-CoV-2 variants. sgRNA was quantified in 169 clinical samples by real-time reverse-transcription polymerase chain reaction, demonstrating similar relative abundance among known variants. Thus, sgRNA detection can identify individuals with active viral replication regardless of variant.